2013
DOI: 10.1111/ppa.12032
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber mosaic virus populations in Tunisian pepper crops are mainly composed of virus reassortants with resistance‐breaking properties

Abstract: Cucumber mosaic virus is one of the most prevalent viruses in Tunisian pepper crops, where it has been detected in 68% of plants developing mosaic symptoms, making it essential to characterize the molecular and biological properties of local CMV populations. Two hundred and seventy-eight isolates collected in the late 1990s, 2006 and 2008-2010 were characterized genetically. Isolates belonging to the three phylogenetic subgroups of CMV (IA, IB and II) were detected, but surprisingly, 90% of the isolates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…5). A recent genetic study of CMV populations of pepper in South Korea identified geographically distinct subpopulations , a phenomenon also reported in Tunisia (Ben Tamarzizt et al, 2013). Genetic diversities in the Korean populations were highest at 0.060 in the 1a ORF and lowest at 0.029 in the MP ORF .…”
Section: Discussionmentioning
confidence: 91%
“…5). A recent genetic study of CMV populations of pepper in South Korea identified geographically distinct subpopulations , a phenomenon also reported in Tunisia (Ben Tamarzizt et al, 2013). Genetic diversities in the Korean populations were highest at 0.060 in the 1a ORF and lowest at 0.029 in the MP ORF .…”
Section: Discussionmentioning
confidence: 91%
“…This suggests that it would be more biologically significant to focus on the effect of recombination on between‐host transmission. However, the rate of transmission of aphid‐transmitted plant viruses, including CMV, has been shown repeatedly to correlate with accumulation in the infected host (Escriu et al ., ; Betancourt et al ., ), establishing a link between the within‐host and between‐host components of virus fitness. The messenger/viral RNA recombinant becomes predominant in the viral population Detailed analyses of the genetic structure of field populations of CMV in different regions of the world have shown the presence of isolates generated by genetic exchange by both reassortment of genomic segments and by recombination within each segment (Bonnet et al ., ; Ben Tamarzizt et al ., ; Nouri et al ., ). However, the frequency of recombinants was always low, even under conditions in which this would not be attributed to random genetic drift (Bonnet et al ., ).…”
Section: Evaluation Of Whether Recombination In Plants Expressing a Cmentioning
confidence: 99%
“…shown the presence of isolates generated by genetic exchange by both reassortment of genomic segments and by recombination within each segment (Bonnet et al, 2005;Ben Tamarzizt et al, 2013;Nouri et al, 2014). However, the frequency of recombinants was always low, even under conditions in which this would not be attributed to random genetic drift (Bonnet et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polygenic resistance to CMV, combining several QTLs (quantitative trait loci) acting on different steps of plant infection, has been used to create highly resistant pepper cultivars, including F 1 hybrids (Caranta et al, 1997a(Caranta et al, , 2002Palloix & Ordon, 2011). However, a recent epidemiological survey in Tunisia showed that several CMV isolates were adapted to the resistant pepper cultivar Milord (Ben Tamarzizt et al, 2013). One common property shared by all CMV isolates virulent towards pepper resistance was the fact that they had a subgroup IB-type RNA 1.…”
Section: Discussionmentioning
confidence: 99%